Website Quality and its Impact on Customer Satisfaction and Purchase Intention in the E-Commerce Sector in India - Sanjiv Mittal (International Journal of Intelligent Systems and Applications in Engineering, 2024)
“E-commerce is on the rise both in India and abroad as the economy is becoming digital and consumers are using online platforms to search for information and for making purchases of different types of services and products. Retail e-commerce sales were 5.2 trillion Dollars approximately worldwide in 2021. It is forecasted that this figure will grow by 56 percent over the next few years, and reach 8.1 trillion dollars by 2026. (as per Global retail e-commerce sales 2014-2026, Published by Stephanie Chevalier, Sep 21, 2022). Websites are an important component of the rapidly growing E-commerce market. In the overall marketing communication mix, the websites complement the direct selling activities, helps to improve the corporate image and provide basic information about the company to its customers using an online platform. There is a need to study the measures of Website designs which help to improve their quality as well as the customer satisfaction towards the website design of the company, which may also lead to purchase intention of the consumer. Customer reaction to the website has been studied by the author taking into consideration the Amazon India and Flipkart websites as they are comparable names. Study was conducted in Delhi-NCR and data was gathered from 658 respondents out of which 300 were from Delhi 358 were from NCR covering the areas – Gurgaon, Noida, Ghaziabad, Faridabad etc. The construct used to collect the data was a standard construct – WebQualtm, a measure of Website quality. 12 dimensions of WebQualtm were taken into consideration to study the satisfaction of customers towards the Website Quality of Amazon and Flipkart. Another linkage that was studied was whether this customer satisfaction towards Website quality led to purchase Intention among the Customers or not. PLS-SEM was used for analysing the hypothesized relationship among the constructs and was found that Website Quality significantly influenced the Customer Satisfaction which in turn leads to Purchase intention of the customer.”